2011
DOI: 10.1055/s-0031-1280373
|View full text |Cite
|
Sign up to set email alerts
|

Spirostanol Saponins Derivated from the Seeds ofTrigonella foenum-graecumbyβ-Glucosidase Hydrolysis and Their Inhibitory Effects on Rat Platelet Aggregation

Abstract: Nine spirostanol saponins (1-9) and seven mixtures of 25 R and 25 S spirostanol saponin isomers (10-16) were obtained from the seeds of Trigonella foenum-graecum after enzymatic hydrolysis of the furostanol saponin fraction by β-glucosidase. Their structures were determined by NMR and MS spectroscopy. Among them, 1- 4, 6, 8, and 9 were new compounds and five, 11B, 12A, 13B, 14A, and 14B, were new structures observed from seven mixtures. In addition, the inhibitory effects of all saponins on rat platelet aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…9, 15, 17), being the main source of diosgenin released during acid hydrolysis. It has been reported that 25S and 25R sapogenins mutually epimerize (5,27,28); therefore, under acidic conditions, yamogenin may be converted to diosgenin.…”
Section: Hplc-elsd-esi-ms Separationmentioning
confidence: 99%
See 2 more Smart Citations
“…9, 15, 17), being the main source of diosgenin released during acid hydrolysis. It has been reported that 25S and 25R sapogenins mutually epimerize (5,27,28); therefore, under acidic conditions, yamogenin may be converted to diosgenin.…”
Section: Hplc-elsd-esi-ms Separationmentioning
confidence: 99%
“…Fenugreek (Trigonella foenum-graecum, Fabaceae) is an annual, herbaceous plant, originating from the Mediterranean region and cultivated all over Europe. Fenugreek seeds are known to contain several groups of secondary metabolites, of which, besides flavones (1,2), isoflavones (1) and polysaccharides (3), the most abundant are steroidal saponins (2,(4)(5)(6)(7)(8)(9)(10)(11)(12). The complex of steroidal saponins in fenugreek seeds is composed of different spirostanol and furostanol saponins with straight or branched sugar chains (2,(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed extraction and isolation of the 25 (R/S)-spirostanol saponin diastereomers was described elsewhere [9]. The structures of the six 25 R/S diastereomers used in this study are shown in Fig.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Also, a purified fraction prepared from Fenugreek seeds which contained more than 90% steroid saponins enhanced food consumption and induced hypercholesterolaemia in experimental rats [19]. Recently [27], spirostanol saponin aglycones, obtained from Fenugreek seed by enzymatic hydrolysis, were shown to inhibit platelet aggregation in rats. The potential of plant (and animal) steroids as antiviral agents was reviewed elsewhere [28].…”
Section: Introductionmentioning
confidence: 99%